Low‐CCN concentration air masses over the eastern North Atlantic: Seasonality, meteorology, and drivers. Issue 2 (30th January 2017) - Wood, Robert; Stemmler, Jayson D.; Rémillard, Jasmine; Jefferson, Anne
Abstract: A 20 month cloud condensation nucleus concentration ( N CCN ) data set from Graciosa Island (39°N, 28°W) in the remote North Atlantic is used to characterize air masses with low cloud condensation nuclei (CCN) concentrations. Low‐CCN events are defined as 6 h periods with mean N CCN <20 cm −3 (0.1% supersaturation). A total of 47 low‐CCN events are identified. Surface, satellite, and reanalysis data are used to explore the meteorological and cloud context for low‐CCN air masses. Low‐CCN events occur in all seasons, but their frequency was 3 times higher in December–May than during June–November. Composites show that many of the low‐CCN events had a common meteorological basis that involves southerly low‐level flow and rather low wind speeds at Graciosa. Anomalously low pressure is situated to the west of Graciosa during these events, but back trajectories and lagged SLP composites indicate that low‐CCN air masses often originate as cold air outbreaks to the north and west of Graciosa. Low‐CCN events were associated with low cloud droplet concentrations ( N d ) at Graciosa, but liquid water path (LWP) during low‐CCN events was not systematically different from that at other times. Satellite N d and LWP estimates from MODIS collocated with Lagrangian back trajectories show systematically lower N d and higher LWP several days prior to arrival at Graciosa, consistent with the hypothesis that observed low‐CCN air masses are often formed by coalescence scavenging in thick warm clouds, often in cold air outbreaks. Key Points: A 20 month cloud condensation nuclei (CCN) data set from the Azores is used to identify air masses with very low concentrations Low‐CCN air masses tend to occur during winter and spring and are often associated with cold air outbreaks occurring upstream of the Azores Liquid water path enhancement upstream of air mass arrival at the Azores can account for low concentrations via coalescence scavenging